Study on the Relationship between Anatomical Structure and Drought Resistance of Six Prunus persica - Chujie, Zhang; Zahra, Aqsa E; Mastoi, Abdul Hafeez; Alam, Aitazaz; Amjad, Aqsa; Masoom, Muhammad; Rasool, Muhammad Wajahat; Ahmed, Mian Muhammad; Rehmani, Urooj; Saleem, Muhammad; Conglin, Xi (Journal of Agriculture and Biology, 2025)
Six main peach tree varieties in Shanxi Province were selected as the test materials. Branches of six peach tree varieties were sectionized in paraffin, and their anatomical structures were observed and analyzed. Anatomical structure characteristics such as epidermal thickness, thickness of thick horn tissue, vascular bundle, ratio of xylem to stem area, and number of catheterization were selected as evaluation indexes for drought resistance. The method of fuzzy mathematical membership function analysis was used to comprehensively evaluate its drought resistance. The results showed that the drought resistance of six main peach tree varieties were as follows: Pinggu 14> Qinwang> Jinyumi> Jinhongmi> Hongfenghuang, thus providing scientific reference for the breeding and management of peach tree varieties in our province.
Keywords: Peach Varieties; Paraffin production; Drought resistance; Anatomical characteristics